Discourses from Latin America and the Caribbean Current Concepts and Challenges - Esposito, Eleonora; Pérez-Arredondo, Carolina; Ferreiro, José Manuel (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited collection brings together the latest research on discourse and society in Latin America and Caribbean in one volume. Employing cross-cutting approaches to current political, institutional and media discourses, it bridges existing theoretical and analytical gaps between the socio-political macro issues and the micro aspects of linguistic analysis to provide fresh insights that deconstruct the complex socio-political power dynamics in Latin America and the Caribbean. Across eight chapters this volume explores the regions' thorny relationship with their complex histories of colonialism and slavery as well as the ongoing, multifaceted constructions of hegemonic and counter-hegemonic identities at the individual, regional and national levels. In doing so, it demonstrates the unique and rich particularities of these regions and why it is that they challenge many conventional dogmas and methods across the Social Sciences. This book will be of particular interest to scholars working in Discourse Studies, Sociology, Politics, Anthropology and Latin American and Caribbean Studies.